Role of Mobile Banking in Bridging the Urban-Rural Financial Gap: Evidence from Gandaki Province - Khanal, Rajiv (Devkota Journal of Interdisciplinary Studies, 2025)
This study examines the impact of mobile banking on financial inclusion across urban and rural areas of Gandaki Province, Nepal. Despite national progress in expanding formal financial services, rural populations continue to face barriers such as geographic isolation, limited digital literacy, and distrust in financial institutions, which sustain disparities in access to banking services. Mobile banking offers a promising approach to bridge this gap by providing accessible, cost-effective, and secure financial services via mobile devices. A mixed-methods research design was employed, combining quantitative data collected from 792 respondents with qualitative insights from interviews and focus group discussions. Five key factors access to mobile technology, educational attainment, socioeconomic status, perceived security of mobile banking, and frequency of mobile banking usage were hypothesized to influence financial inclusion. Structural Equation Modeling (SEM) using SmartPLS was applied to test these relationships, with adequate model fit confirmed by multiple indices. The results indicate that in urban settings all five factors significantly contribute to financial inclusion. In contrast, in rural areas, only socioeconomic status, perceived security, and mobile banking usage frequency were positively associated with financial inclusion. Notably, access to mobile technology and education level did not significantly affect rural financial inclusion, with education exhibiting a negative relationship, possibly reflecting migration effects or unmet expectations among educated rural residents. These findings underscore the importance of context-specific strategies, including infrastructure improvement, digital literacy programs tailored to rural needs, and trust-building measures, to enhance equitable financial inclusion. The study advances understanding of mobile banking adoption by applying TAM and UTAUT frameworks to distinct geographic contexts within Nepal